Vivências do envelhecer em comunidade: velhices no espaço de cultura e solidariedade do Jardim da Conquista - Sousa, Vilma Machado de (2012)
The far-reaching limits of Gerontology field of knowledge confirm the importance of this research, which aims to study the ageing process as related to the concept of ageing well and seeking a good quality of life during old age, considering the community life led by elders on a daily basis. Ten elderly individuals, regulars at Solidarity and Culture Center, residents in Jardim da Conquista neighborhood, Eastern São Paulo City, were selected. A group of 62 to 81 year old male and female individuals answered a survey, which included personal data and semistructured questions about their sociocultural profile and their experience in the Solidarity and Culture Center. The chosen methodology, qualitative approach, focused on investigating the elderly living conditions and how they practice their citizenship skills, exercising their rights in centers for community life. Gerontology and associated fields of knowledge provided theoretical references to support this research. Its findings acknowledged the significant role played by community life in improving the elderly living condition and in changing the way they see their own ageing process. It s worth mentioning that when facing the challenge of living possible and actual ageing experiences on a daily basis, the elderly end up bringing a new meaning to the ageing process